2018
DOI: 10.15537/smj.2018.6.22950
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipocalin-2 oncogene and its impact on gene polymorphisms on breast cancer patients in Jeddah, Saudi Arabia

Abstract: Objectives:To identify the impact of Lipocalin-2 (LCN2) gene polymorphisms on breast cancer patients in Jeddah, Saudi Arabia.Methods:It is a case control study in which blood samples of participants from Medical Reference Clinics and King Abdulaziz University Hospital in Jeddah, Saudi Arabia have been taken between 2014 and 2016. This study recruited 128 participants (50% control, 50% patients) and used Tetra-Primer amplification-refractory mutation system-polymerase chain reaction method for the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…A study conducted among Hong Kong Chinese individuals revealed an association between the rs3814526 SNP of LCN2 and hypertension ( Ong et al, 2011 ). Conversely, research involving breast cancer patients indicated elevated levels of LCN2 protein bothin the plasma and breast cancer cells compared to controls, although no significant correlation was observed with polymorphisms in the LCN2 gene ( Linjawi et al, 2018 ). Our findings suggest a potential therapeutic mechanism whereby the SGLT2 inhibitor dapagliflozin may target the rs3099844 SNP of the LCN2 gene to inhibit LCN2 expression in the treatment of IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among Hong Kong Chinese individuals revealed an association between the rs3814526 SNP of LCN2 and hypertension ( Ong et al, 2011 ). Conversely, research involving breast cancer patients indicated elevated levels of LCN2 protein bothin the plasma and breast cancer cells compared to controls, although no significant correlation was observed with polymorphisms in the LCN2 gene ( Linjawi et al, 2018 ). Our findings suggest a potential therapeutic mechanism whereby the SGLT2 inhibitor dapagliflozin may target the rs3099844 SNP of the LCN2 gene to inhibit LCN2 expression in the treatment of IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LCN2 expression was significantly higher in inflammatory BCa (IBC) tumors regardless of the molecular subtype than in non-inflammatory BCa tumors. In patients with inflammatory BCa, increased expression of LCN2 is associated with poor prognosis and a lower overall survival rate ( Linjawi et al, 2018 ). The in vivo and in vitro studies by Yan et al found that LCN2 is highly expressed in fat cells, which leads to insulin resistance.…”
Section: Adipokines and Breast Cancermentioning
confidence: 99%